Peningkatan kemampuan pemecahan masalah matematis siswa melalui penerapan model pembelajaran missouri mathematic project - Harianda, Boni; Junedi, Beni (Journal of Didactic Mathematics, 2021)
Problem solving is a basic skill that should be possessed by students. Mathematical problem solving abilities play a role in solving every problem both other subjects and problems in everyday life. Through mathematical problem solving activities students are directed to build mathematical knowledge, think logically, systematically and measurably. The fact is that students' mathematical problem solving abilities are still low. The learning process that focuses on exercises that provide opportunities for students to develop mathematical problem solving skills to become a model for improvement in the learning process. The Missouri Mathematical Project learning model is an appropriate learning model to facilitate students in developing their thinking in solving mathematical problem solving problems. For this reason, this study aims to improve students' mathematical problem solving abilities through the application of the Missouri mathematical learning model. This type of research is a classroom action research (PTK). The research subjects were grade V students of MIS Al Firdausy Pematang Reba. The data collection technique used was a mathematical problem-solving ability test. The data analysis technique used is quantitative data analysis. Based on the results of the test of mathematical problem solving abilities, there was an increase in each cycle starting from the initial pre-action test, cycle I and cycle II. It can be concluded that there is an increase in students' mathematical problem solving abilities through the application of the Missouri mathematical learning model.